Pengaruh Perbedaan Padat Penampungan Dan Dosis Pakan Alami Terhadap Pertumbuhan Larva Udang Windu (Penaeus monodon Fab.) [ The Effect Of Density And Natural Feed Dozes Growth Of Giant Shrimp Larvae (Penaeus monodon Fab.) ] - Hendri Gustrifandi (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract The growth of shrimp larvae are depend on several factors, such as natural feed. These natural feed must consist protein, carbohydrate and lipid to support survival rate. The best growth of post larvae of giant shrimp are found by Artemia sp. as natural feed, whereas number of Artemia sp. 75 sp/day can support growth of shrimp 6.901 gr/species.